PENGARUH PRAKTIKUM BERWAWASAN LINGKUNGAN DENGAN MODEL INKUIRI TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR - Siti Maesarah; Baiq Asma Nufida (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This study aims to determine the effect of the experiment based environmentalon scientific attitude of the student and learning achievement on acidandalkali subject. This study was quasi-experimental with Posttest-Only ControlGroup Design. The sample consists of two intact group, experimental group(learning by experiment based environmental method) and control group(learning by traditional method) choosen by purposive sampling technic. Datacollection of scientific attitude using questionnaires and observation sheets,while learning outcomes data collected by an objective test. Data analyzedwith descriptive statistic and non parametric statistic (Mann Whitney test).The result show that student’s scientific attitude score of experiment group is83.35 at very high category while the control group is 77.82 at the highcategory. The average score of learning achievement 86.40 for experimentalgroup higher than control groupis 70.87. Beside that Mann-Whitney testobtained sig. less than 0.05 (p <0.005). Thus, it can be concluded that theexperiment based environmental methods affect the scientific attitude andstudent learning achievement on acid-base subject.